Differences of Blood Glucose Levels in Diabetes Mellitus Patients Consuming Brown Rice and White Rice - Rahmasari , Ikrima; Fidayani, Yuli; Huwaida, Hasna (International Journal of Psychosocial Rehabilitation, 2026)
Diet is an important determinant that influences the occurrence of insulin resistance. Thus, eating patterns greatly influence the occurrence of DM disease. Micronutrient substances and phytochemicals in brown rice are higher than white rice, so brown rice likely has a protective effect on the incidence of type 2 diabetes. This study used an experimental method using a two-group post-test design with purposive sampling technique. Samples, as many as 32 respondents were divided into two groups of 16 respondents each. The variables of blood glucose levels were analyzed univariately; then subsequently, the bivariate analysis was employed to determine differences in the dependent and independent variables by using the Mann Whitney test with a significance level of 0.05 (5%). The results of this study indicated that the majority of DM sufferers who consumed brown rice had lower blood glucose levels than those who consumed white rice. It was also supported by the results of the Mann Whitney statistical analysis, which obtained a significance value of 0.006